2021
DOI: 10.3390/jcm10235541
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postoperative Hyphemas between Microhook Ab Interno Trabeculotomy and iStent Using a New Hyphema Scoring System

Abstract: We have been using our in-house scoring system of hyphemas, i.e., Shimane University RLC postoperative hyphema scoring system (SU-RLC), which we designed to classify postoperative hyphema. SU-RLC classifies the severities of hyphemas based on three factors, i.e., red blood cells (RBCs) (R) 0–3, layer formation (L) 0–3, and clot (C) 0–1, by slit-lamp observation. To test the clinical usefulness of the SU-RLC for quantifying the postoperative hyphema severity, the SU-RLC scores were compared between eyes that un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…We found that the frequency of early postoperative layered hyphema and the SU-R score were significantly higher in the TMH-CE group compared to the Inject-CE group. In a previous study, we reported higher hyphema scores in eyes that underwent TMH compared to eyes implanted with the first-generation iStent on postoperative days 1, 2, and 3 [13]. Our current study revealed that postoperative hyphema is even less common with the second-generation iStent than with the TMH.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…We found that the frequency of early postoperative layered hyphema and the SU-R score were significantly higher in the TMH-CE group compared to the Inject-CE group. In a previous study, we reported higher hyphema scores in eyes that underwent TMH compared to eyes implanted with the first-generation iStent on postoperative days 1, 2, and 3 [13]. Our current study revealed that postoperative hyphema is even less common with the second-generation iStent than with the TMH.…”
Section: Discussionsupporting
confidence: 58%
“…The severity of each hyphema was estimated and given an R score according to the Shimane University Hyphema Scoring System (SU-R) [13]. This system, which is specifically designed to classify postoperative hyphema, categorizes the floating red blood cells (RBCs) in AC from 0 to 3.…”
Section: Participantsmentioning
confidence: 99%
“…Similarly, the incidence of hyphema was more common following goniotomy with a 360-degree incision than with a 120-degree incision [12,13]. In our previous research, we reported higher hyphema scores in eyes undergoing TMH than in those receiving first-and secondgeneration iStent implants during the early postoperative period [19,29]. These findings suggest that the severity of hyphema correlates with the extent of incision width following angle surgeries.…”
Section: Discussionmentioning
confidence: 54%
“…The Shimane University Postoperative Hyphema Scoring system (SU-RLC) [19] is utilized to assess the severity of hyphema. This method evaluates hyphema severity through a slit-lamp examination, focusing on three primary elements: red blood cells (RBCs) (R), layering (L), and clot formation (C).…”
Section: Measurementsmentioning
confidence: 99%
“…The surgical procedure was performed through two corneal side ports as reported previously [10,11]. Before iStent implantation, phacoemulsification cataract surgery was performed through a 2.2-mm-wide clear corneal incision created at the 9 to 10 o'clock position (i.e., temporal incision for the right eye and nasal incision for the left eye); a one-piece soft acrylic IOL (non-toric or toric) was inserted into the capsular bag through the same clear corneal incision.…”
Section: Surgical Proceduresmentioning
confidence: 99%